STRUCTURAL SHIFT IN PUBLIC EXPENDITURE ON HIGHER EDUCATION IN INDIA AND KERALA IN THE REFORM PERIOD - Dr. NASIYA V K (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper examines whether there is a structural shift in public expenditure on education in general and the higher education in particular during the reform period since 1991 as compared to the pre-reform period. In order to examine this, here considered public expenditure data for the period from 1975/6 to 2018/19. For the convenience of analysis, the data sorted for two periods namely pre-reform period, 1975/76-1990/91 and reform period, 1991/92- 2018/19. This classification is made based on the availability of secondary data from various sources like MHRD and Budget Documents of Central and State governments. The basic postulate is that there is a structural shift in the form of a decline in public expenditure on education in general and higher education in particular during the reform period. Further the argument that there is a structural break in public expenditure on education, is examined by Chow Break Point Test by taking 1991/92 as the break year